Molecular docking study of 2,4 disubstituted thiazole derivatives as antiulcer activity - Wadave, D.B.; S.C. Daswadkar, (International Journal of Biology and Chemistry, 2024)
In this study, 2,4 disubstituted thiazole derivatives were used to create an antiulcer agent. These compounds were chosen based on molecular properties and a drug-likeness score, ensuring their suitability for oral absorption. The molecular docking of 2,4 disubstituted thiazole derivatives was performed using AutoDock Vina Ver.1.1.2. The thiazole derivatives were constructed using Cambridge's Chem Draw Ultra 8.0 software. The program Chem 3D Ultra 8.0 was used to convert 2D structures to 3D structures. Thiazole derivatives were docked into the H2 blocker, with nizatidine binding at the active site (PDB ID: 2XZB) as the target protein obtained from the protein data bank. The current study reported anti-ulcer activity of newly synthesized derivatives with electron releasing and electron withdrawing groups on thiazole derivative. The study provided potential derivatives exhibiting significant anti-ulcer activity with fast onset and extended duration of action, which is the most promising expectation of any anti-ulcer agent, especially when administered in conjunction with complaint-specific therapy.